Identifikasi Senyawa Metabolit Sekunder dan Penetapan Kadar Total Flavonoid Ekstrak Etanol Daun Gatal (Laportea Stimulans) - Cut Bidara Panita Umar; Lukman La Bassy; Syamsudin Kelutur (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Determination of total flavonoid levels is calculated based on the linear regression equation based on the calibration curve of the quercetin standard solution from the reading results of the UV-Vis spectrophotometry tool. The absorbance value (ppm) is entered into the linear regression formula as the y value, while the x value is the concentration of flavonoids in the working sample solution. The results are stated in triplicate and the flavonoid content is stated with the equivalence of flavonoid standards using quercetin standard standards, qualitative and quantitative research methods to determine metabolite compounds and determination of levels using UV-vis spectrophotometry. Qualitative testing is carried out by taking a thick extract and adding reagents according to the identified compounds. Based on the results of the tests carried out, it shows that alkaloid, flavonoid, steroid, triterpenoid, tannin, and saponin compounds show positive results while quinone compounds show negative results. Quantitative testing From the results of this study, the total flavonoid content of the ethanol extract of itching leaves (Laportea stimulans) was 175.961%. Based on the results of qualitative tests, it shows that the ethanol extract of itchy leaves (Laportea stimulants) positively contains several compounds including alkaloids, flavonoids, steroids, terpenoids, tannins, and saponins which are indicated by changes in color. Based on the results of quantitative tests, it shows that the determination of the content of 95% ethanol extract of itchy leaves (Laportea stimulants) spectrophotometrically at a wavelength of 430 nm has an average total flavonoid content of 0.2999%.